2003
DOI: 10.1124/mol.64.5.1189
|View full text |Cite
|
Sign up to set email alerts
|

Ceramide Is Involved in R(+)-Methanandamide-Induced Cyclooxygenase-2 Expression in Human Neuroglioma Cells

Abstract: Cannabinoids have recently been shown to induce the expression of the cyclooxygenase-2 (COX-2) isoenzyme in H4 human neuroglioma cells. Using this cell line, the present study investigates the contribution of the second messenger ceramide to this signaling pathway. Incubation of cells with the endocannabinoid analog R(ϩ)-methanandamide (R(ϩ)-MA) was associated with an increase of intracellular ceramide levels. Enhancement of ceramide formation by R(ϩ)-MA was abolished by fumonisin B 1 , a ceramide synthase inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
2
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 42 publications
4
49
2
2
Order By: Relevance
“…p38 is not involved in N-acetyl phytosphingosine -mediated COX-2 expression but does play a role in tetra-acetyl phytosphingosine -mediated expression. Other reports indicate that induction of COX-2 is ERK-and p38-dependent (36,37). We did not find p38 dependence of COX-2 accumulation in resveratrol-treated MCF-7 cells (Fig.…”
Section: B Mcf-7 Cells Were Treated With 10contrasting
confidence: 48%
See 1 more Smart Citation
“…p38 is not involved in N-acetyl phytosphingosine -mediated COX-2 expression but does play a role in tetra-acetyl phytosphingosine -mediated expression. Other reports indicate that induction of COX-2 is ERK-and p38-dependent (36,37). We did not find p38 dependence of COX-2 accumulation in resveratrol-treated MCF-7 cells (Fig.…”
Section: B Mcf-7 Cells Were Treated With 10contrasting
confidence: 48%
“…Ramer et al (37) have shown that R(+)-methanandamide induces COX-2 expression in human neuroglioma cells via production of ceramide. Treatment of human mammary epithelial cells with C 2 -ceramide increases levels of COX-2 protein and mRNA and enhances prostaglandin E 2 synthesis (42).…”
Section: B Mcf-7 Cells Were Treated With 10mentioning
confidence: 99%
“…With respect to the observed CB receptor dependency of COX-2 expression by both cannabinoids, our data contradict previous observations from our group showing a receptor-independent induction of COX-2 expression by both cannabinoids in human non-pigmented ciliary epithelial [11] and neuroglioma cells [27][28][29]42] and for MA in human cervical carcinoma cells [30]. Thus, dependent on the cell type, cannabinoids may use either receptor-dependent or -independent pathways to confer increased synthesis of A c c e p t e d M a n u s c r i p t 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 20 PGs which may on the one hand depend on extracellular activation of membrane-bound receptors and might otherwise rely on a lipid raft-dependent intracellular uptake [29].…”
Section: Confirmation Of the Proposed Antimigratory Mechanism By Use contrasting
confidence: 88%
“…Based on our previous investigations demonstrating cannabinoids as potent inductors of COX-2 expression in diverse cell types [11,[27][28][29][30][31]] and on the above mentioned interference of NSAIDs with the IOP-lowering action of cannabinoids, we were particularily interested in the role of COX-2 and one of its potential downstream targets, the tissue inhibitor of matrix metalloproteinases-1 (TIMP-1), in this process. Here we show that the antimigratory action of the phytocannabinoid THC and the stable endocannabinoid analogue MA on human TM cells is conferred by a COX-2-dependent upregulation of TIMP-1.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have been undertaken in other cell lines where this pathway has been interrupted which has resulted in a reduction in cell toxicity (Carracedo et al 2006;Ramer et al 2003). Both the specific ceramide synthase inhibitor fumonisin B1 (Wattenberg et al 1996), and myriocin (ISP-1) that inhibits serine palmitoyltransferase which is needed for de novo synthesis of ceramide (Miyake et al 1995), per se and in combination attenuated HU 210-induced cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%